The Anatomy of the Firm Size Distribution: The Evolution of its Variance and Skewness - Peter Huber; Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 2007)
The evolution of higher moments of the firm size distribution so far seems to be neglected in the empirical firm growth literature. Based on GMM estimates, this paper introduces simple Wald tests to investigate whether the firm size distribution converges in both the second and third central moment. Using a comprehensive sample of Austrian firms, the estimation results indicate a substantial reduction in both the second and third central moment for the younger age cohorts. This effect is much less pronounced for older firms. Across age cohorts one observes an increase in variance, while the third central moment tends to vanish.
Keywords: 330; Growth of firms; market concentration; moments of the firm size distribution; GMM estimation; Wald test; Unternehmenserfolg; Marktmacht; Momentenmethode; Schätzung; Österreich